2008
DOI: 10.1120/jacmp.v9i3.2747
|View full text |Cite
|
Sign up to set email alerts
|

Time‐course of effects of external beam radiation on [18F]FDG uptake in healthy tissue and bone marrow

Abstract: The utility of PET for monitoring responses to radiation therapy have been complicated by metabolically active processes in surrounding normal tissues. We examined the time‐course of [18F]FDG uptake in normal tissues using small animal‐dedicated PET during the 2 month period following external beam radiation. Four mice received 12 Gy of external beam radiation, in a single fraction to the left half of the body. Small animal [18F]FDG‐PET scans were acquired for each mouse at 0 (pre‐radiation), 1, 2, 3, 4, 5, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In addition to gastrointestinal tract, 18 F-FDG PET/CT imaging can also be utilized to investigate the effects of radiation on other parts of the body such as bone marrow metabolism [27, 41, 42]. Our results agrees with these findings and further demonstrate that 18 F-FDG PET/CT imaging can detect radiation-induced metabolic changes in the event of accidental exposure, which can be critical for determining survival.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to gastrointestinal tract, 18 F-FDG PET/CT imaging can also be utilized to investigate the effects of radiation on other parts of the body such as bone marrow metabolism [27, 41, 42]. Our results agrees with these findings and further demonstrate that 18 F-FDG PET/CT imaging can detect radiation-induced metabolic changes in the event of accidental exposure, which can be critical for determining survival.…”
Section: Discussionsupporting
confidence: 85%
“…A long-term consequence after radiotherapy may be a reduction up to −5% of cerebral metabolic activity in the irradiated brain tissue, as compared to non-irradiated brain tissue 65 .…”
Section: Imaging Findingsmentioning
confidence: 99%
“…It is generally understood that FDG studies should be performed 2-3 months after radiation therapy to avoid the acute effects of post-radiation therapy inflammation (33). However, the effects of external-beam radiation therapy can be variable and depend on the amount and time course of radiation delivered (34). One review of patients with cancer and pericardial disease found that radiation-induced pericarditis is relatively rare and present in only 10% of patients, compared with benign idiopathic pericarditis in 32% and malignant pericardial disease in 58% (35).…”
Section: Pericardiummentioning
confidence: 99%